Para la salcedocoronelización de la Fábula de Equis y Zeda - Garrote Bernal, Gaspar (Dicenda. Estudios de lengua y literatura españolas, 2008)
Fábula de Equis y Zeda has been considered text of irrational construction and therefore of difficult or impossible comment. Starting from three keys of Gerardo Diego (cubist or creationist militancy, dedication to the study of gongoristic and after-gongoristic poetry, and recovery of the genre of mythological fable), Equis y Zeda is revealed here as poem whose argument depends on intertextuality of a certain composition that Gabriel Bocángel published in La lira de las musas (1637)